Myeloid‐derived suppressor cells mediate tolerance induction in autoimmune disease. Issue 1 (2nd March 2017) - Wegner, Anja; Verhagen, Johan; Wraith, David C.
Summary: In multiple sclerosis (MS) T cells aberrantly recognize self‐peptides of the myelin sheath and attack the central nervous system (CNS). Antigen‐specific peptide immunotherapy, which aims to restore tolerance while avoiding the use of non‐specific immunosuppressive drugs, is a promising approach to combat autoimmune disease, but the cellular mechanisms behind successful therapy remain poorly understood. Myeloid‐derived suppressor cells (MDSCs) have been studied intensively in the field of cancer and to a lesser extent in autoimmunity. Because of their suppressive effect on the immune system in cancer, we hypothesized that the development of MDSCs and their interaction with CD4 + T cells could be beneficial for antigen‐specific immunotherapy. Hence, changes in the quantity, phenotype and function of MDSCs during tolerance induction in our model of MS were evaluated. We reveal, for the first time, an involvement of a subset of MDSCs, known as polymorphonuclear (PMN)‐MDSCs, in the process of tolerance induction. PMN‐MDSCs were shown to adopt a more suppressive phenotype during peptide immunotherapy and inhibit CD4 + T‐cell proliferation in a cell‐contact‐dependent manner, mediated by arginase‐1. Moreover, increased numbers of tolerogenic PMN‐MDSCs, such as observed over the course of peptide immunotherapy, were demonstrated to provide protection from disease in a model of experimental autoimmune encephalomyelitis. Abstract : In this manuscript we reveal a novel role for myeloid‐derived suppressor cells in antigen‐specific immunotherapy in a model of experimental autoimmune encephalomyelitis.